(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. The severity of recurrence of injuries in track and field athletics gives possibility to adjust training programs for athletes. Research aim was to analyse which body parts are mostly injured and the severity of recurrence of injuries in track and field athletics gives possibility to adjust training programs for athletes. Research methods. Thirty six athletes were given questionnaires developed using standardized methodology validated by the IOC and implemented by the IAAF during international track and field competitions. Research results. There were 64 cases of injuries among 33 athletes: head and trunk cases – 12 (18.8%), upper extremity – 14 (21.9%), lower extremity – 38 (59.4%). In all cases lower extremity injuries dominated. In sprinters lower extremity injuries dominated and there was no upper extremity trauma. In throwers the upper and the lower extremity were equally vulnerable, mild and very mild injuries were observed. There was no difference between both groups in recurrence of the same trauma. Discussion and conclusions. Estimating which body parts are mostly injured in sports gives the possibility to adjust training programs for athletes, increasing the amount of athletic exercises intended for the functional preparation of those parts. Injuries in track and field are frequent and dominating injuries are of lower extremity; there exist the possibility of recurrence of the injury in the same body part. Injuries prevalent in sprinter cohort are of lower extremities, and injuries prevalent in throwing cohort are of lower and upper extremities. Keywords: physiotherapy, Parkinson’s disease, reaction time.